Pengaturan Sistem dan Mekanisme E-Voting Pemilihan Kepala Desa (Pilkades) - Yohanes Paulus Syukur; Hernimus Ratu Udju; Yonas S. O. Benu (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the legal aspects in the application of the e-voting system in the election of village heads as a form of technological innovation in voting. With a normative legal approach, this research is based on relevant laws and regulations, including Law Number 6 of 2014 concerning Villages and its amendments in Law Number 3 of 2024. The results of the study show that the e-voting regulation is not explicitly contained in the law, but gives authority to local governments to design village head election policies, which is strengthened by the Constitutional Court Decision Number 147/PUU-VII/2009. In addition, the e-voting mechanism meets the principle of legality in the elections, emphasizes the principle of luberjurdil, and is in line with democratic values. The conclusion of this study emphasizes that the implementation of the election with the e-voting method can be applied by paying attention to the legal standards and cumulative requirements that have been set.